2020
DOI: 10.1177/1464420720966347
|View full text |Cite
|
Sign up to set email alerts
|

Selection of sustainable material for the manufacturing of complex automotive products using a new hybrid Goal Programming Model for Best Worst Method–Proximity Indexed Value method

Abstract: Selection of the most suitable sustainable material to fulfill the requirements of a product in a specific application is a complex task. Material selection problems are basically multi-criteria decision making problems as selection of the optimal material is based on the evaluation of conflicting criteria. Considering the limitations such as ranking reversal problem of the various multi-criteria decision making methods available in the literature, a combination of two recently developed techniques, i.e. the G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…Using equation (31) to calculate the normalized matrix, the calculated results were presented in Table 18. Using equation (32) to calculate the normalized matrix with weight.…”
Section: Multi-criteria Decision Making Using the Moora Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using equation (31) to calculate the normalized matrix, the calculated results were presented in Table 18. Using equation (32) to calculate the normalized matrix with weight.…”
Section: Multi-criteria Decision Making Using the Moora Methodsmentioning
confidence: 99%
“…Fifthly, PIV is a method for multi-criteria decision making, firstly introduced in 2018 [7]. This method has been successfully applied in multi-criteria decision making in some cases, such as in the ranking and selection of E-learning sites [30], for the selection of materials to manufacture some parts of automobiles [31], for the selection of elements in logistics activities of the EU countries [32], for the selection of additives in a production process [33]. However, up to now, no studies have been found to apply this method for multi-criteria decision making in the turning process.…”
Section: Introductionmentioning
confidence: 99%
“…Since, PIV is a newly developed method, the ranking results obtained from PIV method are compared with the ranks obtained with existing methods namely weighted aggregated sum product assessment (WASPAS), technique for order by preference by similarity to ideal solution (TOPSIS), Evaluation based on distance from average solution (EDAS), Range of value (ROV) and Complex proportional assessment (COPRAS) method. The details of these methods can be found in literature [52][53][54][55][56][57]. The ranking results are shown in Table 9.…”
Section: Comparison With Other Mcdm Methodsmentioning
confidence: 99%
“…Zhang et al (2017) applied the hybrid analytic network process (ANP) decision making trial and evaluation laboratory (DEMATEL) (DEMATEL-ANP) and grey relational analysis (GRA) technique for selecting the green materials considering the economic, environmental, and physical properties as major input criteria. Wakeel et al (2020) applied best worst method and proximity indexed value method as a goal programming model. The hybrid method was used to select the possible material for manufacturing a complex automobile part for which F1 race car as advanced automotive its gearbox casing as sensitive part was used on the available alternative materials aluminum, magnesium, titanium, and carbon fiber/epoxy laminate.…”
Section: Introductionmentioning
confidence: 99%